FAO, Banco Mundial e a política pública de regularização fundiária do estado do Piauí: um estudo de caso sobre a influência das organizações internacionais no ciclo da política pública - Silva Junior, Cosmo da (2022)
This research sought to analyze how International Organizations (IOs) influence the formulation of public policies in the domestic context. In this sense, the general objective of this study is to understand the role of the Food and Agriculture Organization of the United Nations (FAO) and the World Bank in the formulation process of the new Land Regularization Policy of the state of Piauí enacted in 2019 through law nº. 7.294/2019. To this end, a historical overview of the formation of the Piauí territory was traced to arrive at the state's current problem, which is land control by foreign and national capital and its socio-environmental impacts. Subsequently, it was inquired, from the literature review, about the instruments used by International Organizations to spread their ideals and influence the cycle of public policy in the domestic context. Finally, following a qualitative approach, a case study was conducted adopting, as a data collection technique, documentary research and open interviews, having as analytical parameter the theoretical model designed by Jakobi (2009). We conclude the study arguing that FAO, by means of the argumentative dissemination and behavior configuration instruments, acted by disseminating the Voluntary Guidelines for the Responsible Governance of Land, Fisheries and Forest Resources - DVGT; and that the World Bank, by means of financial aid instruments, technical support and coordination functions, also influenced the process that culminated in the new Land Regularization Policy of the State of Piauí.